Maternal care and birth outcomes among ethnic minority women in Finland - Gissler Mika; Malin Maili (BMC, 2009)
Abstract Background Care during pregnancy and labour is of great importance in every culture. Studies show that people of migrant origin have barriers to obtaining accessible and good quality care compared to people in the host society. The aim of this study is to compare the access to and use of maternity services, and their outcomes among ethnic minority women having a singleton birth in Finland. Methods The study is based on data from the Finnish Medical Birth Register in 1999-2001 linked with the information of Statistics Finland on woman's country of birth, citizenship and mother tongue. Our study data included 6,532 women of foreign origin (3.9% of all singletons) giving singleton birth in Finland during 1999-2001 (compared to 158,469 Finnish origin singletons). Results Most women have migrated during the last fifteen years, mainly from Russia, Baltic countries, Somalia and East Europe. Migrant origin women participated substantially in prenatal care. Interventions performed or needed during pregnancy and childbirth varied between ethnic groups. Women of African and Somali origin had most health problems resulted in the highest perinatal mortality rates. Women from East Europe, the Middle East, North Africa and Somalia had a significant risk of low birth weight and small for gestational age newborns. Most premature newborns were found among women from the Middle East, North Africa and South Asia. Primiparous women from Africa, Somalia and Latin America and Caribbean had most caesarean sections while newborns of Latin American origin had more interventions after birth. Conclusion Despite good general coverage of maternal care among migrant origin women, there were clear variations in the type of treatment given to them or needed by them. African origin women had the most health problems during pregnancy and childbirth and the worst perinatal outcomes indicating the urgent need of targeted preventive and special care. These study results do not confirm either healthy migrant effect or epidemiological paradox according to which migrant origin women have considerable good birth outcomes.